Remote Accountants' Role in Advancing United Nations Sustainable Development Goals: The Case of a Philippine Fund Services Company - Benavides, Crizabel Mye A.; Jubahib, Mary Jean G.; Encarguis, Ana Belen B.; Briones, Jesus P.; Abante, Marmelo V. (Journal of Social Entrepreneurship Theory and Practice, 2024)
Remote accountants who work from any location with Internet access and leverage digital tools and cloud-based systems contribute to the value creation and sustainability of organizations. This study evaluated the role of remote accountants in advancing United Nations Sustainable Development Goals (SDGs) 8 (Decent Work and Economic Growth), 9 (Industry, Innovation, and Infrastructure), and 10 (Reducing Inequality). A structured questionnaire was used to gather data from 60 remote accountants in a Philippine fund service company, with descriptive correlational methods applied to identify patterns. The findings revealed active engagement among remote accountants in supporting sustainable practices, innovation, and inclusion although various organizational challenges persist. The study also disclosed the existence of significant relationship between the role of accountants in financial reporting and their contribution to advancing SDGs. However, it was found that there is no significant relationship between their role relative to financial reporting and the barriers to advancing SDGs. Similarly, no significant relationship was noted between their contribution to SDGs and barriers to advancing SDGs. This study proposes strategic recommendations to enhance investment accuracy, technology adoption, and workforce skills to address these challenges. Key initiatives include specialized training, resource optimization, technological upskilling, and the promotion of fair practices to strengthen inclusion and equality. Finally, the study affirmed the strategic role that remote accountants could assume in driving sustainability in financial services and pointed out investment and policy directions where improvements could be sought to optimize sustainability.